Home Visit: The Rejection of Forced Online Learning by Islamic Religious Education Teachers During the COVID-19 Pandemic - Suyadi, Suyadi; Huda, Miftachul (Universitas Muhammadiyah Magelang, 2022)
Online learning has caused psychosocial trauma and decreased students’ achievement during the Covid-19 pandemic, hence, Islamic Education (IE) teachers conducted home visits as an alternative learning activity. Therefore, this study aims to analyze the teachers' rejection of online learning and discusses a new model of home visits. This is a qualitative study with a phenomenology approach, and the participants were Islamic Education Teachers in the Yogyakarta Special Region, Indonesia. The data were collected through observation, interview, as well as online documentation, and analyzed using description, interpretation, and meaning creativity. The results showed online learning during the pandemic was carried out regardless of the students' mental health. Furthermore, the home visit program encompasses Islamic religion learning and therapy, especially for those suffering from psychosocial trauma. This visit can be adapted to solve more complex students’ psychosocial conditions even after the Covid-19 pandemic.